Psocoptera (Insecta: Psocodea) from the National Natural Park Gorgona, Cauca, Colombia - Sarria-S, Fabio; González O., Ranulfo; García Aldrete, Alfonso Neri (Revista de Biología Tropical, 2014)
The Psocoptera fauna of Gorgona National Natural Park, Colombian pacific, consists of 75 species in 42 genera and 21 families. 1 730 specimens were collected in the period November 2007-June 2011. Five families, 20 genera and nine species are new records for Colombia, and two genera and ten species are new to science. The psocid fauna of the island constitutes an extension of the continental fauna. Rev. Biol. Trop. 62 (Suppl. 1): 243-256. Epub 2014 February 01.